Synergistic Mechanism of the High-Quality Development of the Urban Digital Economy from Blockchain Adoption Perspective—A Configuration Approach - Ming Xia; Zhimin Xie; Hui Lin; Xiangwu He (Journal of Theoretical and Applied Electronic Commerce Research, 2022)
Blockchain technology is suited to the high-quality development of the digital economy in addressing privacy and data security issues. This study explores the synergistic mechanism of the following six factors from three dimensions based on the Technology-Organization-Environment (TOE) framework theory with a fuzzy set qualitative comparative analysis (fs/QCA) method: technology, organization, and environment, namely, Blockchain service capability, Blockchain knowledge accumulation, government attention allocation, government funding support, industry carrying capacity and blockchain technology R&D environment, on the quality of the digital economy of 43 cities in China. The conclusions are as follows: (1) the absence of government funding regarding the blockchain domain is a condition contributing to the absence of high urban digital economy quality; (2) there are three driving configurations for the high-quality urban digital economy in the blockchain technology adoption perspective, which are as follows: knowledge-industry driven, government-service driven, and R&D-service driven; (3) there is one driving configuration for the absence of high urban digital economy quality, namely the knowledge-R&D-funding-inhibiting type. The relevant policy implications can provide theoretical references for local governments to develop the digital economy with the help of blockchain technology.